Artificial intelligence and the transformation of management education - Toutain, Olivier; Jabbouri, Rachid; Truong, Yann (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
We develop a conceptual framework to examine the potential impact of artificial intelligence (AI) and its associated technologies on five dimensions of management education. Through the analysis of the mission statement of 785 educational technology startups, we identify five mechanisms through which AI may benefit and transform the field of management education in a post-COVID-19 world. Our research is one of the first to propose a global and comprehensive framework to advance our understanding of the impact of a disruptive technology on the traditional and immutable field of higher-education, and more particularly on management education.